On Kitsch in Nature & Technology: Redefining Kitsch for Posthuman Feminist Aesthetics - Casey, Kris (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
This research makes a case for a shift from thinking of kitsch as a phenomenon extending from the industrial revolution, to one that is considered preternatural, existing as a state of being or a process of becoming. This re-theorization co-opts the pejorative connotations of ‘bad’, ‘trash’, and ‘imitation’ and ‘failure’ into positive processes and useful metaphors for contemporary aesthetics, particularly for feminist aesthetics. Its ultimate goal is to articulate an aesthetic theory for Posthuman Feminist Aesthetics and to redefine kitsch as it exists in media culture.